Development of a Potent Antimicrobial Peptide With Photodynamic Activity - Zhang, Di; Chen, Jingyi; Jing, Qian; Chen, Zheng; Ullah, Azeem; Jiang, Longguang; Zheng, Ke; Yuan, Cai; Huang, Mingdong (Frontiers in Microbiology, 2021)
The emergence of antibiotic resistant bacteria posts a serious challenge to medical practice worldwide. A small peptide with sequence RWRWRW was previously identified as a core antimicrobial peptide with limited antimicrobial spectrum to bacteria, especially Gram-positive bacteria. By conjugating this peptide and its analogues with lipophilic phthalocyanine (Pc), we identified a new antibiotic peptide (PcG3K5(RW)3). The peptide demonstrates increased antimicrobial effect to both Gram-positive S. aureus and Gram-negative E. coli. In addition, phthalocyanine also provides photocytotoxicity upon red light illumination. The inhibitory efficacy of PcG3K5(RW)3 was increased by ~140-fold to nanomolar range upon illumination. Moreover, PcG3K5(RW)3 was safe to mammalian cell, and promoted wound healing in mice infection model. Our work provides a new direction to optimize antimicrobial peptides to enhance antimicrobial efficacy.